2016
DOI: 10.1016/j.jvs.2016.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and risk factors for bowel ischemia after abdominal aortic aneurysm repair

Abstract: Introduction Bowel ischemia is a rare but devastating complication following abdominal aortic aneurysm (AAA) repair. Its rarity has prohibited extensive risk factor analysis, particularly since the widespread adoption of endovascular repair (EVAR). Therefore, the purpose of this study was to assess the incidence of postoperative bowel ischemia following AAA repair in the endovascular era, and identify risk factors for its occurrence. Methods All patients undergoing AAA repair, either intact or ruptured, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 26 publications
6
59
1
2
Order By: Relevance
“…Old age (HR 1.13), hyperlipidaemia (HR 4.61) and ADT (HR 3.32) were associated with ischaemic stroke. Ultee et al 32 also reported an increased risk for bowel ischaemia in smokers, leading to COPD 11. Longstreth et al found that acute large bowel ischaemia is independently associated with COPD (adjusted OR 3.13) 10.…”
Section: Discussionmentioning
confidence: 96%
“…Old age (HR 1.13), hyperlipidaemia (HR 4.61) and ADT (HR 3.32) were associated with ischaemic stroke. Ultee et al 32 also reported an increased risk for bowel ischaemia in smokers, leading to COPD 11. Longstreth et al found that acute large bowel ischaemia is independently associated with COPD (adjusted OR 3.13) 10.…”
Section: Discussionmentioning
confidence: 96%
“…62 Risk factors include advanced age, female sex, hypertension, heart failure, and prolonged procedure time. 63 Bowel ischemia has a poor outcome and is associated with 34.6% mortality. 63 The risk is lower in elective compared to emergent repair.…”
Section: Bowel Ischemiamentioning
confidence: 99%
“…63 Bowel ischemia has a poor outcome and is associated with 34.6% mortality. 63 The risk is lower in elective compared to emergent repair. 64 Careful evaluation of the mesenteric arteries and collateral flow to the colon is crucial to avoid such a complication.…”
Section: Bowel Ischemiamentioning
confidence: 99%
“…На 3-и сутки в связи с развитием перитонита, обусловленного некрозом терминального отдела подвздошной и восходящей ободочной кишки без [1,9,10]. По данным литературы, ОННМК после резекции АИСА встречается в 0,2-1 % случаев [10,16], является трудно диагностируемым, смертельно опасным осложнением с плохим прогнозом и летальностью, достигающей в ряде наблюдений 100 % [3,4].…”
unclassified
“…Наиболее частой причиной развития нарушения мезентериального кровообращения у больных, перенесших резекцию АИСА, является острая окклюзия ранее проходимых висцеральных артерий вследствие их эмболии и тромбоза [2,16]. Реже наблюдается ОННМК вследствие мезентериальной гипоперфузии и ангиоспазма, факторами риска развития которых являются низкий сердечный выброс, адреномиметическая терапия, шок, гиповолемия, гипотония, хронический гемодиализ, операции на сердце и аорте [10].…”
unclassified